Investigation of solar assisted heat pump system integrated with high-rise residential buildings - Fu, Yu (2014)
The wide uses of solar energy technology (solar thermal collector, photovoltaic and heat pump systems) have been known for centuries. These technologies are intended to supply domestic hot water and electricity. However, these technologies still face some barriers along with fast development. In this regards, the hybrid energy system combines two or more alternative technologies to help to increase the total efficiency of the system. Solar assisted heat pump systems (SAHP) and photovoltaic/thermal collector heat pump systems (PV/T-HP) are hybrid systems that convert solar radiation to thermal energy and electricity, respectively. Furthermore, they absorb heat first, and then release heat in the condenser for domestic heating and cooling.